Analysing digital campaigns of nationalist parties in Indonesia through political party tweets - Ahmad Muhardin Hadmar; Shintia Yuniarti; Achmad Nurmandi; Herman Lawelai; Anwar Sadat; Misran (Faculty of Communications Science, Dr. Soetomo University, 2024)
Twitter is the main platform for digital campaigns that influence public opinion. Through Twitter, political parties reach a wider audience to disseminate messages effectively. This research analyses narrative content on social media as a medium for political party campaigns delivered via social media. This research examines the campaign content strategy of nationalist party Twitter accounts in Indonesia. The method used is a qualitative method utilising Quality Data Analysis (QDA) with the help of Nvivo 12 Plus software. Three nationalist party Twitter accounts were taken based on their popularity, particularly @Gerindra, @Nasdem, and @PDI_Perjuangan. The @Gerindra account with 68.1 thousand followers highlights aspects of the party's identity and the figure of Prabowo Subianto. In contrast, the @NasDem account focuses more on party identity, national issues, and active participation in political society. The @PDI_Perjuangan account focuses on the spirit of struggle, the candidacy of Ganjar Pranowo, and the construction of the party's identity and history, with high activity, namely 1219 tweets in three months. The results of the analysis of the content of nationalist party Twitter accounts can provide insight into political party communication strategies in digital campaigns in Indonesia.